Crystallization of DNA‐Capped Gold Nanoparticles in High‐Concentration, Divalent Salt Environments1. Issue 5 (20th December 2013) - Tan, Shawn J.; Kahn, Jason S.; Derrien, Thomas L.; Campolongo, Michael J.; Zhao, Mervin; Smilgies, Detlef‐M.; Luo, Dan
Abstract The multiparametric nature of nanoparticle self‐assembly makes it challenging to circumvent the instabilities that lead to aggregation and achieve crystallization under extreme conditions. By using non‐base‐pairing DNA as a model ligand instead of the typical base‐pairing design for programmability, long‐range 2D DNA–gold nanoparticle crystals can be obtained at extremely high salt concentrations and in a divalent salt environment. The interparticle spacings in these 2D nanoparticle crystals can be engineered and further tuned based on an empirical model incorporating the parameters of ligand length and ionic strength.